2017
DOI: 10.2527/jas.2017.1522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multi-strain Bacillus spp. direct-fed microbial and a protease enzyme on growth performance, nutrient digestibility, blood characteristics, fecal microbiota, and noxious gas emissions of grower pigs fed corn-soybean-meal-based diets—A meta-analysis1

Abstract: Three studies involving 352 grower pigs were conducted to determine the effects of dietary supplementation with multistrain spp. direct-fed microbial (DFM) and protease, alone or in combination, on growth performance, nutrient digestibility, blood characteristics, fecal microbiota, and noxious gas emissions, and to use a meta-analysis to increase the reliability of the findings. Treatments ( = 4) were set up as a 2 × 2 factorial design with 2 levels of protease (0 and 5.000/6.000 units/kilogram of feed [U/KG])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
7
3
1
Order By: Relevance
“…A similar study by Wilson et al (2019) did not observe CST improve BW, ADG, or DMI during either the receiving or finishing periods; however, CST-supplemented cattle tended to have improved feed efficiency over both feeding periods. Bacillus subtilis PB6 DFM alone and in combination with other Bacillus organism DFM have been reported to improve growth performance and gut integrity of nursery pigs ( Cai et al, 2015 ; Brooks and Kim, 2017 ; Payling et al, 2017 ) and have anticlostridial activity against the causative pathogen in necrotic enteritis of poultry ( Teo and Tan, 2005 ). Given the limited existing literature in beef cattle, further research in supplementing B. subtilis PB6 is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study by Wilson et al (2019) did not observe CST improve BW, ADG, or DMI during either the receiving or finishing periods; however, CST-supplemented cattle tended to have improved feed efficiency over both feeding periods. Bacillus subtilis PB6 DFM alone and in combination with other Bacillus organism DFM have been reported to improve growth performance and gut integrity of nursery pigs ( Cai et al, 2015 ; Brooks and Kim, 2017 ; Payling et al, 2017 ) and have anticlostridial activity against the causative pathogen in necrotic enteritis of poultry ( Teo and Tan, 2005 ). Given the limited existing literature in beef cattle, further research in supplementing B. subtilis PB6 is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…The MULTI did not affect growth performance of growing-finishing pigs during the overall experimental period (Table 2). Most previous studies showed that pigs fed diets with dietary protease or probiotics had higher growth rate of pigs than those fed diets without dietary protease or probiotics [2,7,9,2528]. However, some research reported that addition of dietary protease or probiotics in pig diets did not affect growth rate of pigs [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Addition of protease in pig diets is a way to improve protein utilization. The main mechanism of dietary protease is to increase the hydrolysis of proteins in the small intestine [1], resulting in liberating amino acids and peptides for utilization and absorption by pigs [2]. Previous studies showed that dietary protease in pig diets decreased the nitrogen (N) pollution by enhancing N digestibility of pigs and reducing N excretion of pigs [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotic supplementation has been used to overcome the above-mentioned problems [ 12 - 14 ]. Probiotics can accelerate the breakdown of the carbohydrates which are resistant to digestion, thus it encourages the use of dietary fiber as a prebiotic substance, and promotes the substrate availability of colonic microbiota, and its population [ 15 ]. It has been extensively studied probiotics are able to support growth performance, gut micro-environment, feed utilization efficiency, immune system, and gastrointestinal tract (GIT) diseases for farm animals [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%